Penerapan Manajemen Resiko pada Pembangunan Proyek Perpanjangan Dermaga log (Studi Kasus: Pelabuhan DalamTanjung Emas Semarang) - Ismiyati, Ismiyati; Sanggawuri, Ranggi; Handajani, Mudjiastuti (Department of Civil Engineering, Diponegoro University, 2019)
Delay in the implementation of the project often occurs due to various risk factors that have not been identified during project implementation, so that the impact on project delays and unexpected costs increases. However, each construction project has different risks, becaused the environmental conditions of the project, so that it requires handling different methods of project implementation. This study aims to: 1) analyze the risks that could potentially occur during the construction of the log dock extension; 2) Appropriate Handling Methods for the Implementation of the Log Dock Extension Work. The research method is done by identifying the risks that occur in the field and with the interview method about the possibility of possible risks that occur. The results of the study indicate five high-risk categories according to the perception of service providers that most influence on project delays. These risks include unpredictable external phenomena, such as tidal elevations that exceed plan, resulting in changes in design and method of implementation. The conclusions of this study include that the application of risk management to the implementation of the log dock extension project at the port of Tanjung Emas Semarang needs to be applied to minimize delays and reduce unexpected costs.